Model Komunikasi Dakwah Jamaah Tabligh - Ujang Saepuloh (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2009)
Jama’ah Tabligh constitutes one of da’wah organizations in Indonesian that has many unique characteristics. Besides its da’wah movement that different of organisational da’wah in a general way, this organisation also has typical symbols of its fellow men. Aspects that can be recognized from this jama’ah at least cover three: (1) da’wah movement pattern named khuruj, which is sticking out, far from home, (2) configurational figures that do ever pet beard, putting on elongated cloth, bounding up head with cloth and always use pants upon ankle, (3) da’wah communication models that by large develope: da’watul-ifrodi communication model, da’watul-ijtima’i communication model, da’watul khususi wal-umumi communication model.